COMPENSATION INCREASES EMPLOYEE PRODUCTIVITY AT PT. BUSSAN AUTO FINANCE (BAF) JAYAPURA - Yomungga, Moses; Sarangan, Ester (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
Compensation is one of the factors that can enhance work productivity in a company. This is also applicable to the financial company PT. Bussan Auto Finance (BAF) Jayapura. This study aims to evaluate how the reward system provided to employees affects their productivity levels in carrying out duties and responsibilities within the company. Additionally, it seeks to understand the extent of the influence of compensation on employee productivity levels. The method used is a quantitative approach by applying Regression Analysis to test the relationship partially. The results indicated that compensation has a partial positive impact on the productivity of PT. BAF employees. This is evidenced by a t-value of 3.511 with a significance level of 0.001, demonstrating that an increase of one unit in compensation will enhance productivity by 35.11%. Furthermore, incentives also have a partial positive effect on the productivity of PT. BAF employees. The regression analysis results showed a t-value of 2.521 with a significance level of 0.014, indicating that an increase of one unit in incentives will boost productivity by 25.21%. Therefore, it is crucial to maintain and improve the incentive system. The combined effect of compensation and incentives on productivity also showed positive results. The regression analysis demonstrated that both factors significantly contribute to productivity, with the regression equation: Y = 1.239 + 0.786(X1) + 0.308(X2).